2008
DOI: 10.1152/ajpcell.00490.2007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for KCNQ1 K+ channel expression in rat zymogen granule membranes and involvement in cholecystokinin-induced pancreatic acinar secretion

Abstract: Lee W-K, Torchalski B, Roussa E, Thévenod F. Evidence for KCNQ1 K ϩ channel expression in rat zymogen granule membranes and involvement in cholecystokinin-induced pancreatic acinar secretion. Am J Physiol Cell Physiol 294: C879-C892, 2008. First published January 23, 2008 doi:10.1152/ajpcell.00490.2007.-Secretion of enzymes and fluid induced by Ca 2ϩ in pancreatic acini is not completely understood and may involve activation of ion conductive pathways in zymogen granule (ZG) membranes. We hypothesized that a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 60 publications
2
17
3
Order By: Relevance
“…19,20,26,27 By several GWA studies, KCNQ1 has been identified as a transethnic susceptibility gene for T2D. 6 Genetic variation in KCNQ1 appears to be associated with impaired insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…19,20,26,27 By several GWA studies, KCNQ1 has been identified as a transethnic susceptibility gene for T2D. 6 Genetic variation in KCNQ1 appears to be associated with impaired insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…ZGs from mouse exocrine pancreas were isolated as described in detail elsewhere (Thévenod et al 2003;Lee et al 2008). Briefly, pancreatic tissue from female C57BL/6N mice (15-17 g, fasted overnight) (Charles River Laboratories; Sulzfeld, Germany) was homogenized by nitrogen pressure cavitation and centrifuged on a self-forming Percoll gradient.…”
Section: Isolation Of Zymogen Granules (Zgs) and Purification Of Zgmsmentioning
confidence: 99%
“…These results appeared to oppose the role of Kv7.1 in enzyme secretion from permeabilized rat pancreatic acini described by us in the above study (63). However, we showed that CCK-stimulated enzyme secretion in permeabilized rat pancreatic acini was abolished only if flufenamate was applied together with 293B, which is an indication that several ZG cation channels with functional redundancy are involved in enzyme secretion (63). Lastly, this experiment resolves the controversy with the study on perfused rat pancreas (60) where no effect of Kv7.1 blockers on secretagogue-induced enzyme secretion had been observed.…”
Section: K + Channelscontrasting
confidence: 68%
“…They therefore concluded that Kv7.1 is not essential for secretagogue-mediated secretion of pancreatic acini. These results appeared to oppose the role of Kv7.1 in enzyme secretion from permeabilized rat pancreatic acini described by us in the above study (63). However, we showed that CCK-stimulated enzyme secretion in permeabilized rat pancreatic acini was abolished only if flufenamate was applied together with 293B, which is an indication that several ZG cation channels with functional redundancy are involved in enzyme secretion (63).…”
Section: K + Channelscontrasting
confidence: 59%